2003
DOI: 10.1124/jpet.102.042523
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chloroquine on Renal Function and Vasopressin Secretion: A Nitric Oxide-Dependent Effect

Abstract: We have previously reported that chloroquine administration increases plasma vasopressin concentration and urinary sodium excretion in Sprague-Dawley rats. Because chloroquine has also been shown to stimulate nitric oxide production, the aim of this study was to determine whether nitric oxide mediates chloroquine-induced changes in renal function and secretion of vasopressin. Sprague-Dawley rats (n ϭ 6 -8/group) were infused with 2.5% dextrose under Intraval anesthesia (100 mg kg Ϫ1 i.p.). After 3-h equilibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 26 publications
1
38
0
Order By: Relevance
“…It has been demonstrated that CQ administration results in NO production by the endothelium as well as expression of endothelial nitric oxide synthase in some cell types, leading to renal failure and oxidative distress. [6][7][8] We also found that CQ stimulated the expression of iNOS in DCs WT (Figure 1b). Interestingly, the expression of IDO, an immunomodulatory enzyme, was also elevated, and this effect was observed both in CQ-DCs WT and CQ-DC iNOS 2/2 ( Figure 1b).…”
mentioning
confidence: 63%
“…It has been demonstrated that CQ administration results in NO production by the endothelium as well as expression of endothelial nitric oxide synthase in some cell types, leading to renal failure and oxidative distress. [6][7][8] We also found that CQ stimulated the expression of iNOS in DCs WT (Figure 1b). Interestingly, the expression of IDO, an immunomodulatory enzyme, was also elevated, and this effect was observed both in CQ-DCs WT and CQ-DC iNOS 2/2 ( Figure 1b).…”
mentioning
confidence: 63%
“…Briefly, animals were anesthetized with Intraval (100 mg/kg body wt, thiopentone sodium BP; Rhone-Poulenc Rorer Limited, Nenagh, Co Tipperary, Ireland), and cannulae were inserted into an external jugular vein, carotid artery, and the bladder. Euvolemic fluid replacement of spontaneous urine output was achieved using a servocontrolled fluid replacement system, as described previously (21). Briefly, urine flow rate (UV), determined gravimetrically, is transmitted to an adjustable pump via a computer.…”
Section: Methodsmentioning
confidence: 99%
“…Male OC (4 wk, n ϭ 5 from five litters; 8 wk, n ϭ 9 from six litters) and OD (4 wk, n ϭ 5 from five litters; 8 wk, n ϭ 6 from five litters) were prepared for renal function study as described previously (21). Briefly, animals were anesthetized with Intraval (100 mg/kg body wt, thiopentone sodium BP; Rhone-Poulenc Rorer Limited, Nenagh, Co Tipperary, Ireland), and cannulae were inserted into an external jugular vein, carotid artery, and the bladder.…”
Section: Methodsmentioning
confidence: 99%
“…The TLRs that recognize bacterial and viral nucleic acids (3,(7)(8)(9) are found in the endosomal compartment (4,26) and appear to be trafficking between endosomes and lysosomes (1,14,29). When trafficking and/or acidification is disrupted by chloroquine or bafilomycin A1, TLR signaling is inhibited (1,14,30,32,37).…”
mentioning
confidence: 99%